CD40L‐stimulated B cells for ex‐vivo expansion of polyspecific non‐human primate regulatory T cells for translational studies. (28th December 2020) - Alonso‐Guallart, P.; Llore, N.; Lopes, E.; Kofman, S.‐B.; Ho, S.‐H.; Stern, J.; Pierre, G.; Bruestle, K.; Tang, Q.; Sykes, M.; Griesemer, A.
Summary: The therapeutic applications of regulatory T cells (Tregs ) include treating autoimmune diseases, graft‐ versus ‐host disease and induction of transplantation tolerance. For ex‐vivo expanded Tregs to be used in deceased donor transplantation, they must be able to suppress T cell responses to a broad range of human leukocyte antigen (HLA). Here, we present a novel approach for the expansion of polyspecific Tregs in cynomolgus macaques that was adapted from a good manufacturing practice‐compliant protocol. Tregs were isolated by fluorescence‐activated cell sorting (FACS) and expanded in the presence of a panel of CD40L‐stimulated B cells (CD40L‐sBc). Prior to Treg culture, CD40L‐sBc were expanded in vitro from multiple major histocompatibility complex (MHC)‐disparate macaques. Expanded Tregs expressed high levels of forkhead box protein 3 (FoxP3) and Helios, a high percentage of Treg ‐specific demethylated region (TSDR) demethylation and strong suppression of naïve T cell responses in vitro . In addition, these Tregs produced low levels of inflammatory cytokines and were able to expand post‐cryopreservation. Specificity assays confirmed that these Tregs were suppressive upon activation by any antigen‐presenting cells (APCs) whose MHC was shared by CD40L‐sBc used during expansion, proving that they are polyspecific. We developed an approach for the expansion of highly suppressive cynomolgus macaque polyspecific Tregs through the use of a combination of CD40L‐engineered B cells with the potential to be translated to clinical studies. To our knowledge, this is the first report that uses a pool of MHC‐mismatched CD40L‐sBc to create polyspecific Tregs suitable for use in deceased‐donor transplants. Abstract : We developed an approach for the expansion of Mauritian cynomolgus macaque polyspecific regulatory T cells (Tregs) through the combination of MHC‐mismatched CD40L‐engineered B cells. Expanded Tregs expressed high levels of FoxP3 and Helios, a high percentage of TSDR demethylation, and strong suppression of naïve T cell responses in vitro . This approach has the potential to be translated to clinical studies for deceased‐donor transplants.